Effects of aging time on microstructure, hydrophobic and optical properties of BiFeO3 thin films synthesized via sol-gel method - Baqiah, Hussein Abdullah Hussein; Talib, Zainal Abidin; Shaari, Abdul Halim; Awang Kechik, Mohd Mustafa; Liew, Josephine Ying Chyi; Ibrahim, Noor Baa'yah (Goeller Verlag GmbH, 2018)
BiFeO3 (BFO) films were synthesized with the sol-gel method followed by the spin coating technique using 2-methoxyethanol as solvent and acetylacetone as chelating agent. The effects of aging time (t = 0, 1, 3, 6 days) of the BFO sol on the microstructure, wettability and optical properties of BFO films were investigated by means of X-ray diffraction (XRD), atomic force microscopy (AFM), contact angle (CA) measurement, Uv-vis and photoluminescence. The crystallinity of films was affected by t. Crystallite size of the films changed slightly in the range of 14.2 – 15.2 nm while the lattice parameters clearly varied with t. The average particle size of BFO films ranged between 45.9 and 52.7 nm while the mean square roughness (Rq) varied between 1.0 and 4.2 nm. The films showed maximum optical transmittance (81 – 90 %) in the range 600 – 800 nm. The band gap of the films was also affected with t, and it has a value of 2.85 to 2.76 eV. The films showed a hydrophobic property with CA ranging between 95.3 to 104.7 °. The best crystallinity, lowest Rq and highest Eg = 2.85 eV were obtained for the film with t = 1 day. The results demonstrate possible development of a superhydrophobic coating using BiFeO3 coating.